Factors Affecting Economic Growth - Riza Ronaldo; Heru Subiyantoro; Machfud Sidik; Dedi Bahagia (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Climate change and global warming caused by the increasing number of greenhouse gas emissions can damage human survival, Greenhouse emissions and the economic growth of a country are the main factors that can encourage an increase in the amount of greenhouse gas emissions in the atmosphere, which causes global warming. The study purposed to determine the factors that influence changes in greenhouse emissions and economic growth. The method used in this research is Ordinary Least Square Multiple Linear Regression and simple panel data. The research variables are Energy Consumption, Labor, Loan Interest Rates, and Fuel Eco sport. Those are used as independent variables that affect greenhouse emissions, which function as the dependent variable, and economic growth, which functioned as the dependent variable with the variable Free of Greenhouse Emissions. The results of the study show that (1) energy and labor consumption simultaneously or partially have a significant effect on changes in the number of greenhouse emissions by 89.5% (2) Changes in total greenhouse emissions partially have a significant and positive effect on the country's economic growth (3) research findings. The following variable the increase in the country's Greenhouse Emanation is the most dominant variable with a significant positive effect on a country's economic growth of 70.74 percent